Implementation of Android-Based Blended Learning for Improving Learning Outcome and Information Literacy Skill of Students - Setyoko Setyoko; Tri Mustika Sarjani; Siska Rita Mahyuny; Suryanti Suryanti (Postgraduate, University of Mataram, 2023)
Rapid development of information and communication technology should be accompanied by appropriate changes in learning activities. Implementation of Blended learning is considered providing space for students to learn both offline and online. The use of android media in the activity will facilitate students to learn the materials in a specific, interesting, and easy way. This study aimed to examine the improvement of learning outcome and information literacy skill of students. Research method applied was Quasi Experimental Design with Non-Equivalent Control Group Pretest-Posttest Design. This study was conducted from June to August 2022 in Senior High School 5 Langsa. Population in this study consisted of 60 students, with class sample X.1: 29 students. Sampling technique applied was purposive sampling. Research instruments included Multiple-Choice Test to investigate learning outcome of students and Rubric Assessment for information literacy skill. Data in this research were statistically analyzed using Paired samples t-test; to analyze learning outcome of students, Cluster, and Descriptive test to analyze the indicators of information literacy skill of students. Study result of learning outcome of students was expressed as value (sig) of 0.00 < (Î±) 0.05, hence Ho was rejected and Ha was accepted. Therefore, implementation of android-based Blended Learning was found to significantly improve learning outcome. Furthermore, study results about information literacy skill showed that students: Find and select information (56.77%), Identify the truth of information (62.58%), Retell the information in writing (62.58%), and Communicate information in a presentation (61.29%) with 3 Indicators of Good Category and 1 Moderate Category. To conclude, habituation of learning activity through android-based blended learning is necessary for students of Senior High School 5 Langsa to strengthen their information literacy skill